Li-chăn: A journey of changes - International Livestock Research Institute (International Livestock Research Institute, 2021)
After two and half years of implementation (2019–2021), the ‘Livestock-led interventions towards equitable livelihoods and improved environment in the Northwest Highlands of Vietnam’ or Li-chăn project has resulted in agricultural system transformation in targeted sites in northwest Vietnam through bundled livestock-based interventions covering livelihoods, environment, equity, and market access to benefit highland farming communities.